JNK1 and JNK3: divergent functions in hippocampal metabolic-cognitive function - Oriol Busquets; Triana Espinosa-Jiménez; Miren Ettcheto; Jordi Olloquequi; Mònica Bulló; Eva Carro; José Luis Cantero; Gemma Casadesús; Jaume Folch; Ester Verdaguer; Carme Auladell; Antoni Camins (BMC, 2022)
Abstract Background and aim The appearance of alterations in normal metabolic activity has been increasingly considered a risk factor for the development of sporadic and late-onset neurodegenerative diseases. In this report, we induced chronic metabolic stress by feeding of a high-fat diet (HFD) in order to study its consequences in cognition. We also studied the effects of a loss of function of isoforms 1 and 3 of the c-Jun N-terminal Kinases (JNK), stress and cell death response elements. Methods Animals were fed either with conventional chow or with HFD, from their weaning until their sacrifice at 9 months. Before sacrifice, body weight, intraperitoneal glucose and insulin tolerance test (IP-GTT and IP‑ITT) were performed to evaluate peripheral biometrics. Additionally, cognitive behavioral tests and analysis of spine density were performed to assess cognitive function. Molecular studies were carried out to confirm the effects of metabolic stressors in the hippocampus relative to cognitive loss. Results Our studies demonstrated that HFD in Jnk3 −/− lead to synergetic responses. Loss of function of JNK3 led to increased body weight, especially when exposed to an HFD and they had significantly decreased response to insulin. These mice also showed increased stress in the endoplasmic reticulum and diminished cognitive capacity. However, loss of function of JNK1 promoted normal or heightened energetic metabolism and preserved cognitive function even when chronically metabolically stressed. Conclusions Downregulation of JNK3 does not seem to be a suitable target for the modulation of energetic-cognitive dysregulations while loss of function of JNK1 seems to promote a good metabolic-cognitive profile, just like resistance to the negative effects of chronic feeding with HFD.